Irreversible thermodynamics analysis of ellipsoidal wheat kernel drying, aiming at the evaluation of phenomenological properties. Issue 9 (4th July 2018) - Santos, Gisele Tessari; Fortes, Mauri; Amantea, Rafael Pinheiro; Ferreira, Wanyr Romeo; Martins, José Helvecio
ABSTRACT: Literature data have revealed that wheat kernel stress–strain relationships, thermal conductivity, and specific heat support the assumption of isotropy. Accepting this premise, we show that drying complexity can be reduced by properly defining the kernel shape and an accurate model. Therefore, we present an irreversible thermodynamics procedure for obtaining transport properties of a wheat kernel. The numerical solution of the associated nonlinear conservation equations was based on the Radial Basis Functions method. Drying behavior of both prolate ellipsoidal and spherical grain kernels is presented and compared. The predicted moisture and temperature profiles correlated favorably with experimental drying profiles, obtained for two temperatures of 47 and 67.5°C.